Feature issue introduction: nanocarbon for photonics and optoelectronics - BLAU, WERNER (Optical Society of America, 2012)
Nanocarbons possess a variety of nearly ideal, low-dimensional nanostructures that cause them to attain unique electronic and optical properties. Recent linear and nonlinear spectroscopic and optoelectronic results prove that they have much to offer in the photonics arena. This feature issue presents reviews and research articles in the area of nanocarbon optics and optoelectronics, which help to summarize the emerging broad range of applications and to expand the understanding of their properties.
PUBLISHED
Keywords: Nanocarbon; Photonics; Optoelectronics